Avaliação psicoeducacional na perspectiva de professores : um estudo a partir da teoria histórico-cultural - Aiache, Dayane Teodoro de Oliveira (2015)
This study deals with issues relating to the psychoeducational assessment in the school context and aimed at investigating, with teachers of early years of elementary public education, what is your understanding of the psychoeducational assessment. It consists of a literature and empirical research. In literature we attempted to, at first, to articulate the history of psychology with the practice of psychoeducational assessment, identifying how this entered the school environment; subsequently, we tried to understand how the schooling difficulties are produced within the school context, trying to demystify the perceptions of school problems; and, in order to understand the psychic development process of the child, there was an analysis of the main assumptions of Vygotskian theory in order to understand man in his socio-historical dimension. The empirical research involved two public elementary schools located in the State of Paraná Interior. This study had the participation of ten teachers from the initial grades of elementary school, five of each school. Data were collected through semi-structured interview technique, based on a script containing eight questions. The interviews were analyzed and discussed from the assumptions of Historical-Cultural Psychology. The results allowed us to understand that the research participants understand the psychoeducational evaluation as a process that identifies the difficulty presented by the student, diagnosing the problem. The expectation of the teachers is that the assessment assist the student in his difficulty, solving it, returning to the classroom in a position to start learning. On the other hand, we also expect that the evaluation guide the teacher in their work and claim the presence of the psychologist in the school routine. There is also the expectation that refer students to the multi-functional resources or special education. Regarding the reason that the teachers to provide to the difficulties of student learning and behavior problems were the most frequent. With regard to interventions with the student before forwarding it to review, most teachers reported not undertake any differentiating intervention with this student. On interventions with the student after the psychoeducational assessment process, most teachers said they desist not from their students and continue to try to teach them, seek to put into practice what has been proposed by the professionals. From the analysis of the interviews with the teachers, we observed that although the understanding is that the psychoeducational assessment is for diagnostic purposes, the teachers expect this assessment to assist in their practice with students, helping them to cope with the difficulties your student presents.